Pengelolaan Kinerja Berbasis Balanced Scorecard - Hartini Hartini; Dhani Habibi (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The Effective performance management is a key factor in achieving the strategic goals of government organizations. This study aims to find out how the use of the balanced scorecard in managing performance management at KPPBC TMP Merak by using the perspectives of stakeholders, customer, internal process, and learning and growth and to find out whether using the balanced scorecard can describe success in achieving performance at KPPBC TMP Merak. The research method used is descriptive qualitative research with primary and secondary data collection. Data collection was carried out by means of observation, interviews, and documentation. The results of the study show that the application of the balanced scorecard in managing performance management at KPPBC TMP Merak using the perspectives of stakeholder, customer, internal process, as well as learning and growth is going very well and by using the balanced scorecard success can be described in achieving organizational performance at KPPBC TMP Merak as evidenced by the status of indicator 19 (nineteen) Main Performance Indicators for 2022 which are green (successfully achieved) and Organizational Performance Score (NKO) in 2020 to 2022 worth above 100 with a special title